Fiber-array-based raman hyperspectral imaging for simultaneous, chemically-selective monitoring of particle size and shape of active ingredients in analgesic tablets - Frosch, Timea; Wyrwich, Elisabeth; Yan, Di; Popp, Juergen; Frosch, Torsten (Molecules, 2019)
The particle shape, size and distribution of active pharmaceutical ingredients (API) are relevant quality indicators of pharmaceutical tablets due to their high impact on the manufacturing process. Furthermore, the bioavailability of the APIs from the dosage form depends largely on these characteristics. Routinely, particle size and shape are only analyzed in the powder form, without regard to the effect of the formulation procedure on the particle characteristics. The monitoring of these parameters improves the understanding of the process; therefore, higher quality and better control over the biopharmaceutical profile can be ensured. A new fiber-array-based Raman hyperspectral imaging technique is presented for direct simultaneous in-situ monitoring of three different active pharmaceutical ingredients- acetylsalicylic acid, acetaminophen and caffeine- in analgesic tablets. This novel method enables a chemically selective, noninvasive assessment of the distribution of the active ingredients down to 1 μm spatial resolution. The occurrence of spherical and needle-like particles, as well as agglomerations and the respective particle size ranges, were rapidly determined for two commercially available analgesic tablet types. Subtle differences were observed in comparison between these two tablets. Higher amounts of acetaminophen were visible, more needle-shaped and bigger acetylsalicylic acid particles, and a higher incidence of bigger agglomerations were found in one of the analgesic tablets.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Acetaminophen; Acetylsalicylic acid; API distribution; Caffeine; Chemical imaging; Fiber sensing; Fiber-array; Hyperspectral imaging; Particle shape; Particle size; Pharmaceutical spectroscopy; Raman spectroscopy